CTNI-56. EVALUATING DRUG DISTRIBUTION IN CHILDREN WITH DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) TREATED WITH CONVECTION ENHANCED DRUG DELIVERY. (12th November 2021) - Szychot, Elwira; Bhagawati, Dolin; Gill, Steven; Walker, David; Hyare, Harpreet
Abstract: BACKGROUND: There is currently no method for evaluating drug distribution and tumour coverage using the convection-enhanced drug delivery (CED) technique in Diffuse Intrinsic Pontine Glioma (DIPG). AIMS: To determine an imaging protocol that can be used to assess the distribution of infusate in children with DIPG treated with CED of carboplatin and sodium valproate. METHODS: 12 children with DIPG received between 4–18ml of infusate, through 2 pairs of catheters to encompass tumour volume on 2 days. Volumetric T2W and Diffusion Weighted Imaging (DWI) MRI sequences were performed before and after the first cycle of CED therapy and Apparent Diffusion Coefficient (ADC) maps were calculated. The tumour volume pre and post CED was automatically segmented (ITKSnap) on T2W and ADC on the basis of signal intensity. The ADC maps pre and post infusion were registered and subtracted (FSL) to visualize the infusate distribution. RESULTS: ADC and T2W demonstrated a significant (< 0.001) change in mean tumour volume post-infusion (mean ADC volume pre: 19.8ml, post 24.4ml; mean T2W volume pre 19.4ml, post 23.4ml). A significant correlation (p< 0.001) was observed for the difference in tumour volume and the actual infused volume (ADC, r=0.76, T2W, r=0.70). There was a significant increase (p< 0.001) in mean ADC and mean T2W signal intensity ratio post-infusion, no significant correlation with infusion volume. Finally, pixel-by-pixel subtraction of the ADC maps pre and post infusion visually demonstrated high signal intensity, presumed infusate coverage of the tumour. CONCLUSIONS: ADC and T2W MR sequences could potentially be used to evaluate the volume of distribution of infusate delivered by CED, paramount to ensure tumour coverage and leading to more effective therapy evaluation. This will facilitate the use of CED in future clinical trials.